Design And Optimization Of Multi-Quantum Wells For Gaas Based Vertical Cavity Surface Emitting Lasers - Jasim, Farah Z. (2010)

(untitled)
Device simulations for the electrical and optical characteristics of GaAs based vertical cavity surface emitting lasers (VCSELs) have been investigated. In such lasers, carrier’s leakage and lateral current separation are some of the major problems in VCSEL design. Thus, in this work the design of VCSEL structures including multi quantum wells (MQWs) active region are described and investigated by Integrated System Engineering Technology Computer Aided Design (ISETCAD) device simulator.